Graded shuttle run performance by playing positions in elite female basketball - Strumbelj, B.; Vuckovic, G.; Jakovljevic, S.; Milanovic, Z.; James, N.; Erculj, F. (The Journal of Strength and Conditioning Research, 2015)
A graded shuttle run test was used to assess differences in physiological parameters between playing positions in elite female basketball players. Twenty-four female basketball players (8 guards, 8 forwards, and 8 centers) who played for the senior national teams of Slovenia and Serbia were tested with the 30-15 intermittent fitness test. During the shuttle run, the following physiological parameters were measured: oxygen consumption (VO2), carbon dioxide production (VO2), pulmonary ventilation (VE) breath by breath, respiratory quotient, oxygen pulse as the VO2 vs. HR ratio and [LA-]. No significant differences were found for any of the measures between the 3 playing positions. Although this finding was surprising, future studies should try to determine whether the tactics used in female basketball determine that the interpositional differences seen in male basketball are not evident.